Aramaic incantation bowls in museum collections - Ford, James Nathan, (Magical and Religious Literature of Late Antiquity;, 2020)
The Frau Professor Hilprecht Collection of Babylonian Antiquities at Friedrich-Schiller-Universität Jena houses one of the major European collections of incantation bowls. Forty bowls bear texts written in the Jewish, Manichaean Syriac or Mandaic scripts, and most of the rest (some twenty-five objects) in the Pahlavi script or in various pseudoscripts. The present volume comprises new editions of the Aramaic (and Hebrew) bowl texts based on high-resolution photographs taken by the authors, together with brief descriptions and photographs of the remaining material. New readings are often supported with close-up photographs. The volume is intended to serve as a basis for further study of magic in late Antiquity and of the Late Eastern Aramaic dialects in which the texts were composed.